TEACHING NARRATIVE READING COMPREHENSION BY USING PROBABLE PASSAGE STRATEGY TO THE TENTH GRADE STUDENTS OF MAN 1 PALEMBANG - Hariana Amalia (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2015)
The objective of the study was to find out whether or not there was a significant difference in reading comprehension achievement between the tenth grade students of MAN 1 Palembang who were taught by using Probable Passage and those who were not. The population of the study was the tenth grade students of MAN 1 Palembang in the academic year of 2014/2015. In this study, the writer used quasi experimental design. The sample of the study was taken from purposive sampling. The writer selected X IPS 2 as the control group and X IPS 1 as the experimental group. It consisted of 74 students, 37 students for each of control and experimental group. This study was conducted for about almost two months. There were twelve meetings which spent 70 minutes (2x35 minutes) in each meeting. The instrument used in collecting the data was multiple choices reading comprehension test. The test was administered twice, as the pre-test and post-test for both control and experimental group. The results of the test were analyzed by using independent sample t-test. From the result of independent sample t-test, it was found that there was a significant difference from students’ posttest experimental and control group, since the p-output was lower than 0.05 and t-value was higher than t-table (1.66). It means that teaching narrative reading comprehension by using Probable Passage had a significant effect on the students’ reading comprehension achievement.